Role of innovative entrepreneurship in the economic growth of regions - S. V. Simonov (Вестник университета, 2025)
The article discusses innovations which are one of the main ways to develop innovative entrepreneurship in the region. They act as a fundamental direction for the growth of innovative potential of Russian regions and regional economic systems as the main element of the effective innovative entrepreneurship development in the entity. The conducted research examines basic tools and methods for the formation of an effective mechanism for assessing the role of the phenomenon in question that contributes to the economic growth of regions. The main attention in observing this problem is paid to systematisation of methodological approaches to the study of the innovative entrepreneurship development. The research has a significant impact on the further study of areas for the formation of the innovative potential and innovative development of the region as the basis for increasing the economic growth of the Russian regions. Introduction and use of various assessments, diagnostics and their realisation in the implementation of the innovative entrepreneurship for progressive changes of the region and its economic growth. The results of the study can be used to assess the role of the innovative entrepreneurship in the economic growth of the Russian subjects. It has allowed for a new interpretation of the phenomenon in question as an integrated business management system.